Analisis Faktor yang Berhubungan dengan Pelaksanaan IMD - Herlinda, Evi; Aryawati, Wayan; Yanti, Dhiny Easter; Bustami, Anita; Angelina F, Christin (LPPM Hang Tuah Pekanbaru, 2024)
Early Initiation of Breastfeeding is the process of breastfeeding the baby immediately after birth, where the baby is left to find his own mother's nipple which is done at least one hour immediately after birth. Nationally, the percentage of newborns who received IMD was 82.7% and in North Lampung Regency it reached 95.1%, and at RSD Mayjend HM Hospital. Ryacudu only 33.04% of mothers who successfully perform IMD. Unsuccessful implementation of IMD can have an impact on increasing the high mortality and morbidity rates. This study aimed to determine the factors related to the implementation of IMD at RSD Mayjend HM. Ryacudu, North Lampung Regency in 2023. This research was quantitative with a cross-sectional design. The population in this study were all mothers giving birth at RSD Mayjend HM. Ryacudu, North Lampung Regency in February-March 2023, with a total of 93 people. The sample in this study used a total sampling of 93 people. The research instrument used was a questionnaire and an observation sheet. Data analysis in this study used univariate, bivariate (chi-square), and multivariate (multiple logistic regression). The results of this study indicate that there was a relationship between education (p-value 0.040 and OR 2.630), type of delivery (p-value 0.005 and OR 3.860), knowledge (p-value 0.027 and OR 2.856), attitude (p-value 0.020 and OR 2.951), and support health workers (p-value 0.000 and 5.438) with implementation. There was no relationship between parity (p-value 0.427) and family support (p-value 0.138) with the implementation of IMD. The dominant factor most related to the implementation of IMD was the variable type of delivery with an OR of 12.535. Advice for mothers giving birth either by sectio caesarea or vaginally can play an active role in carrying out IMD, that Mothers can also find information from both print and online media.